Multidentate azomethine series: complexation and bioactivity studies / Prof Dr Hadariah Bahron, Dr Karimah Kassim and Sharifah Rohaiza Syed Omar - Bahron, Hadariah; Kassim, Karimah; Syed Omar, Sharifah Rohaiza (Research Management Institute (RMI), 2011)
Three Schiff bases namely L1: MPD(ovan)₂, L2: triMe-MPD(ovan)₂ and L3: Cl-MPD(ovan)₂ are obtained from the condensation reaction between derivatives of m-phenylenediamine (MPD) with o-vanillin. Complexation with Co(II), Cu(II) and Zn(II) afford novel dinuclear complexes of dimeric nature. Their structures are elucidated using various physicochemical techniques. The Schiff bases are indicated to act as tetradentate ligands in which both oxygen and nitrogen atoms serve as coordination sites for the metal ions. Antibacterial investigations revealed that the complexes are better bactericides than the parent ligands. The IC50 values against liver cells of the complexes are much lower than those of the parent ligands…